Corona virus (COVID- 19) and education for all achievement: artificial intelligence and special education needs- achievements and challenges - Bah, Yahya Muhammed; Artaria, Myrtati Dyah (COUNS-EDU: The International Journal of Counseling and Education, 2020)
The shortage of well-trained teachers especially in special education is a serious problem worldwide. To attain education for all as enshrined in the Sustainable Development Goals (SDGs), there is urgent need for robot ways of solving this problem with grave consequences for the future of children with disabilities and special education needs. Thus, education delivery methods like other services need to be innovative. The purpose of this studi is to examine the achievements and challenges in the application of AI for teaching children with special education needs. This research used the literature review method. The result of this study shows that AI has the power to enhance learning for children with special needs while curbing some of the problems such children are encountering in accessing quality and relevant education. In conclusion the findings revealed some significant achievements and the possibilities of more if the appropriate technologies are applied consistently with the right environment both in schools and homes.